2020
DOI: 10.3389/fnagi.2020.00197
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Mainly Relates to Cognitive Executive Functions and Improves Through Exergame Training in Older Adults: A Secondary Analysis of a 6-Month Randomized Controlled Trial

Abstract: Heart rate variability (HRV) mirrors autonomic nervous system activities and might serve as a parameter to monitor health status in older adults. However, it is currently unknown which functional health measures, including cognitive, physical, and gait performance parameters, are most strongly related to HRV indices. This knowledge would enable implementing HRV assessments into health monitoring routines and training planning for older adults. Simultaneous cognitive–motor and exergame training may be effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 70 publications
(105 reference statements)
0
22
0
Order By: Relevance
“…Concerning the HRV-related parameters, previous studies have primarily measured these parameters in a resting state and have revealed contradictory results. Indeed, a significant increase of older adults’ resting HRV has been previously reported following 6 months of aerobic exercise training (31 ± 5 ms) [ 82 ], 6 weeks [ 83 ] or 6 months [ 84 ] of exergaming-based dance training, as well as 12 months of supervised stretching and aerobic exercise training [ 85 ]. However, Jakubec et al [ 86 ] and Shen et al [ 87 ] failed to report clear HRV improvements following 6 months or 10 weeks of aerobic exercise training, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the HRV-related parameters, previous studies have primarily measured these parameters in a resting state and have revealed contradictory results. Indeed, a significant increase of older adults’ resting HRV has been previously reported following 6 months of aerobic exercise training (31 ± 5 ms) [ 82 ], 6 weeks [ 83 ] or 6 months [ 84 ] of exergaming-based dance training, as well as 12 months of supervised stretching and aerobic exercise training [ 85 ]. However, Jakubec et al [ 86 ] and Shen et al [ 87 ] failed to report clear HRV improvements following 6 months or 10 weeks of aerobic exercise training, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since higher resting HRV was shown to predict better cognitive functioning (Thayer and Lane, 2000 ; Thayer, 2009 ; Lin et al, 2014 ; Crowley Olga et al, 2016 ; Wawrzyniak Andrew et al, 2016 ; Beer Noa et al, 2017 ; Smith et al, 2017 ; Forte et al, 2019 ), higher exercise frequencies might be a central element to be considered in the design of exercise interventions. Regarding the type of training intervention, a recent randomized controlled trial of Eggenberger et al ( 2020 ) has shown, that a cognitive-motor exergame training was able to improve vagally-mediated HRV at rest, whereas a dual-task training paradigm and an exclusively physical training intervention did not affect HRV. Moreover, cognitive executive functioning (i.e., measured by the Trail-Making-Test (TMT)-B) was the most prominent significant predictor of variance in vagally-mediated HRV (i.e., RMSSD, HF; Eggenberger et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the type of training intervention, a recent randomized controlled trial of Eggenberger et al ( 2020 ) has shown, that a cognitive-motor exergame training was able to improve vagally-mediated HRV at rest, whereas a dual-task training paradigm and an exclusively physical training intervention did not affect HRV. Moreover, cognitive executive functioning (i.e., measured by the Trail-Making-Test (TMT)-B) was the most prominent significant predictor of variance in vagally-mediated HRV (i.e., RMSSD, HF; Eggenberger et al, 2020 ). This is consistent with the findings, that cognitively engaging exercises (i.e., simultaneous cognitive-motor training) appear to have the strongest effect on cognition in HOA (Diamond and Ling, 2016 ; Biazus-Sehn et al, 2020 ; Chen et al, 2020 ) and older adults at risk for cognitive impairment and Dementia (Wu et al, 2019 ; Biazus-Sehn et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the vagus nerve is one of several responses systems contributing to the experience of wellbeing, it has a regulatory role over many including the sympathetic nervous system (Porges, 2011;Deuchars et al, 2018), hypothalamic-pituitary adrenal axis (Porges, 2011), immune functioning (Tracey, 2002;Pavlov and Tracey, 2012), brain-gut interactions (Bonaz et al, 2018;Fülling et al, 2019) neurogenesis and epigenetic mechanisms (Follesa et al, 2007;Biggio et al, 2009;O'Leary et al, 2018). Research now links vagal function to positive emotions (Geisler et al, 2010;Kok and Fredrickson, 2010;Kok et al, 2013), meaning and purpose in life (Zilioli et al, 2015;Dang et al, 2021), emotion regulation (Geisler et al, 2010;Williams et al, 2015), executive function (Williams et al, 2019;Eggenberger et al, 2020), psychological flexibility (Kashdan and Rottenberg, 2010;Colzato et al, 2018), prosocial behaviours (Kemp et al, 2012;Geisler et al, 2013;Kok et al, 2013), positive health behaviours (Werner et al, 2015;Young and Benton, 2018), biopsychosocial resilience (Dedoncker et al, 2021), time spent in nature (Richardson et al, 2016;De Brito et al, 2020) and future morbidity and mortality (Hillebrand et al, 2013;Jandackova et al, 2016;Fang et al, 2020). Various theoretical models have been proposed within which these findings have been interpreted.…”
Section: The Vagus Nerve and Wellbeingmentioning
confidence: 99%